Lithoprobe: Geoscience Studies of the Third Dimension - A Co-ordinated National Geoscience Project for the 1980s. Canadian Committee on the Dynamics and Evolution of the Lithosphere (CANDEL) - Keen, C.; Berry, M.; Macqueen, R. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1981)
Summary The Canadian Committee on the Dynam-ics and Evolution of the Lithosphère(CANDEL; see appendix for membership)recommends that LITHOPROBE studiesbe carried out in specific corridors inseveral parts of Canada, selected to solvekey geological problems. Although thepast two decades have witnessed majorconceptual advances in earth sciencethrough plate tectonic models, manyaspects of continental tectonics and evo-lution have resisted application of platetectonic theory. Because the continentscontain most of the world's knownhydrocarbon and mineral resources, con-tinental tectonics is the major challengeto earth science in the 1980s. Canada,with its vast territory and varied geology,is a natural laboratory for these studies. LITHOPROBE involves the use ofcombined geological and geophysicaltechniques to determine the third dimen-sion of crustal geology, by extending andrelating surface geology to structure atcrustal depth. A large bank of innovativetechniques and concepts is available nowfor LtTHOPROBE studies, ranging fromadvanced high resolution seismic tech-niques and deep drilling, to optimum computer-based interprétâtional methodsand geological models of the latest platetectonic concepts. When combined withmore traditional methods, these newtools substantially improve our prospectsfor resolving the three-dimensional struc-tures and evolutionary histories of keygeological targets. The proposed pro-gramme is national in scope, and willinvolve a broad spectrum of earthscientists. Based on regional geological/geophys-ical considerations, a number of LITHO-PROBE transects are suggested withinfive regions: Appalachian Orogen/Me-sozoic Passive Margin, Arctic, EasternCordillera, Western Cordillera and Mod-ern Pacific Margin, and PrécambrienShield. Two areas are tentatively identi-fied for the initial phase of the LITHO-PROBE programme: onshore-offshoreprofiles of the northeast Newfoundlandarea; and the southeastern Cordillera. Foreach area both the surface geology andthe geological/geophysical problems arewell defined. Each area thus holds thepromise of a high initial degree of suc-cess from the completed transects. APrecambrian corridor is of next highestpriority. Key geological problems for allfive regions as well as the details ofmethodology and costs are presented inthe paper. The specific proposals weredeveloped by CANDEL through studygroups. Studies of the depth dimension in rela-tion to surface geological features willprovide the three-dimensional geometryof major rock units and the recognition ofsimilarities between buried geologicalenvironments which may be host toresources, and those exposed at theearth's surface. Indirect benefits includeexchange of ideas and results betweenthose engaged in the search for resour-ces and those involved in basic research,enhanced training of Canadian geo-science students, and increased incen-tives to Canadian industry to developinnovative techniques andinstrumentation. An initial capital investment of about $4million is estimated, with each corridorcosting an additional $6 million on aver-age. Five or six LITHOPROBE corridorscould be completed in five years, andCANDEL considers this to be a realisticgoal. Locations of LITHOPROBE corri-dors and methodology should be contin-ually reviewed and assessed. The cost ofthe programme largely reflects the costsof high resolution seismic reflection andrefraction technology, but also providesfor the application of deep drilling, and ofmore traditional geological/geophysicalmeasurements. CANDEL recommends that appropriatenew funds be identified by NSERC andEMR. Consideration should be given tomechanisms by which funding to theseagencies can be administered to ensurecoordination between studies. Disburse-ment should be guided by a steeringcommittee charged with setting overallpriorities, and composed of government,university and industry representatives.This committee could be supported by aseries of advisory sub-committees, eachsimilarly charged for a particular regionalLITHOPROBE project. LITHOPROBE as a programme for the1960's can provide a focus for thegovernment-, university-, and industry-based Canadian earth science commun-ity to cooperate on a scale never beforeattempted, as the scope of the problemsand challenges demands. It also canconcentrate the national expertise onproblems of interest and significance toall Canadians.